The Effect Of Kinetic Sand Play Therapy On The Fine Motor Skills Of 4-6 Year Old Children At The Dharma Bakti Kindergarten In Bengkulu City - Afni, Nurul; Susanti, Meri Epriana; Aprianti, Delta (Jurnal Kesehatan Mitra Sekawan, 2025)
The development of children aged 4-6 years in physical growth, one of which is fine motor development. According to WHO data (2020), it was reported that 5-25% of children aged 4-6 years experience motor development disorders and in Bengkulu Province in 2023 the coverage decreased compared to 2015 by 64.03% and is still below the target of 80%. The purpose of this study was to determine the effect of kinetic sand play therapy on the fine motor skills of children aged 4-6 years at Dharma Bakti Kindergarten, Bengkulu City. This study used a quasi-experimental two-group pretest posttest with control group design with a sample size of 40 respondents. Consisting of 20 children in the intervention group and 20 children in the control group. Data collection was carried out using the Denver II sheet. Based on the results of the univariate analysis, it was known that before the intervention group was given kinetic sand play therapy, a small portion of respondents (30%) were suspects and after kinetic sand play therapy, all respondents (100%) had normal fine motor development. Bivariate analysis of normality test obtained data that is not normally distributed, namely sig.0.001 <0.05. Homogeneity test obtained homogeneous distribution data results>0.05, namely 0.898, so in this study using the Wilcoxon test to determine the effect of kinetic sand play therapy. The results of the Wilcoxon test obtained a p-value of 0.014 <0.05, this indicates that there is an effect of kinetic sand play therapy on fine motor skills of children aged 4-6 years at Dharma Bakti Kindergarten, Bengkulu City. Researchers suggest that Dharma Bakti Kindergarten educators in Bengkulu City utilize kinetic sand to improve coordination, finger muscle strength, and fine motor development of children aged 4-6 years.